BIOACCUMULATION OF HEAVY METALS IN THE ROMAN SNAIL (HELIX POMATIA) IN THE AREA OF KOSOVSKA MITROVICA - Bulatović, Željko; Jakšić, Tatjana; Pavlović, Maja; Bačević, Nikola (Bulletin of Natural Sciences Research, 2025)
The bioaccumulation of heavy metals in the Roman snail (Helix pomatia Linnaeus, 1758) was investigated in October 2024.  Animals were sampled at the location "Gornje Polje," which is situated near the former "Trepča" plant. The snails were collected by hand and then transported to the laboratory. A total of 34 medium-aged snails and 36 older snails were collected. The snails were dissected, and the content of heavy metals determined in the hemolymph, hepatopancreas, kidney and shell. In addition to analyzing the heavy metal content in the snails, an analysis of the heavy metals content in the soil was performed. The soil was collected in a quantity of 1 dm³ using a shovel and transported to the laboratory. The content of seven elements was examined: Arsenic (As), Copper (Cu), Iron (Fe), Cadmium (Cd), Manganese (Mn), Lead (Pb), and Zinc (Zn). The highest level of accumulation is heavy metal observed in the hepatopancreas. Furthermore, other structures exhibit a significantly high level of accumulation. All of this suggests that snails are a highly useful tool for diagnostic purposes in environmental of heavy metal accumulation. The analysis of heavy metal content was performed at the Public Health Institute of Kosovska Mitrovica.
Keywords: Heavy metal; Hemolymph; Hepatopancreas; Shell; Kidney; Soil